The Teeter-Totter of Regulation and Competition: Balancing the Indian Competition Commission with Sectoral Regulators - Rahul Singh (Washington University Global Studies Law Review, 2009)
A plethora of regulatory authorities overseeing economic regulation has recently emerged in India. Unlike sector-specific regulators, the Indian competition authority, the Competition Commission of India (“Commission”), is of recent vintage. In fact, although the Indian Parliament enacted competition legislation in 2002, the substantive provisions of this law are not yet in force. Pursuant to the legislative framework, the duty of the Commission is to “prevent practices having adverse effect on competition, promote and sustain competition, protect the interests of consumers and ensure freedom of trade carried on by other participants, in markets in India. ” This mandate is extraordinarily wide and overlaps with the jurisdiction of sector-specific regulators such as the petroleum regulator, electricity regulator, insurance regulator, telecom regulator and securities market regulator. This Article deals with the above interface. It analyzes the genesis of regulatory jurisprudence in the Indian context, and compares and contrasts it with the inception of competition law. After using a case study to map the regulation/competition dichotomy, this Article delineates the overlapping jurisdictions manifested in the multiplicity of regulators and their legislative design. The Article has both an exploratory and normative aim. It takes into account international experiences and closely analyzes the framework of competition law as juxtaposed with sector-specific regulators. In keeping with its exploratory goal, this Article critically surveys relevant legislation and finds that, unlike sector-specific regulatory authorities, the Commission combines the twin powers of private enforcement and the ability to pursue claims for damages. It is, therefore, uniquely situated to ensure a robust level of consumer welfare. Normatively, the Article utilizes the methodological tools of law and economics and suggests that the enforcement of competition policy is a sophisticated and specialized field. Accordingly, the Article suggests that in order to reduce transaction costs and efficiently enhance legal certainty and predictability, the realm of competition law enforcement ought to be left in the hands of the Commission. This strategy is in the best interest of both consumers and business entities. Reprinted by permission of the publisher.
Keywords: Administrative law – India; Antitrust law; Competition (Economics); Consumer protection; Judicial review of administrative acts; Regulatory compliance; India